Comprehensive methodological approach to estimating the research component influence on the information economy development - Марич, Максим; Попова, Любов; Холявко, Наталія; Hanzhurenko, Iryna; Коляденко, Світлана; Nitsenko, Vitalii (My University, 2020)
Purpose. To develop and test a comprehensive methodological approach to assessing the impact of the research component on the development of the information economy based on the combination of statistical, index and cluster methods of analysis. Methodology. In the course of the research, a set of general and special methods of cognition was used: content analysis, logical generalization, quantitative and qualitative comparison, taxonomic and index analysis, cluster analysis, graphical visualization, scientific abstraction and systematization. Findings. It has been established that under the conditions of the national economy informatization, there is a dynamic increase in influence of science and R&D on the socio-economic development of the country. A comprehensive methodological approach to assessing the impact of the research component on the information economy development is suggested; its approbation allowed defining key tendencies and identifying the main problems of implementing the country’s scientific potential under conditions of the national economy informatisation. The vectors of improvement of regulatory state influence on the processes of information economy development are offered: neutral-encouraging ones (support of positive dynamics of intensive development of research component parameters), stimulating-supportive ones (resource and information support), initiating-mentoring ones (motivation and coordination of development processes). Originality. During the research, a scientific and methodological approach to a comprehensive assessment of the impact of the research component on the information economy development was developed. Unlike the existing ones, this approach involves: - monitoring of the processes of scientific and technical development of the country – this made it possible to assess the level of conformity of scientific research studies with the requirements of information economy; - index analysis of the dynamics of the research component of the information economy development – it allowed identifying trends in development of the information economy and its research component; - cluster analysis and comparison of the rates of development of the research component of the information economy at the regional level – it identified the regional disparities and deepened the differentiation of measures of stimulating and regulatory state influence according to the specifics of the identified clusters within the national economic system. Practical value. The results of the study can be used by practitioners, scientists, government officials (the Ministry of Education and Science of Ukraine and its structural departments, local governments in the fields of education and science) to monitor the development of the information economy, the impact of R&D on the processes of development of this type of economy. They can be applied for the improvement of measures of state regulatory influence on economic subjects in order to intensify scientific and technical development of the country and bring the results of scientific researches in accordance with the relevant needs of the real economy.
Keywords: information economy; research component; R&D; index analysis; cluster analysis; higher education and science